Aplikasi Mobile Ensiklopedia Dermatologi sebagai Upaya Deteksi Dini Penyakit Kulit - Suryani, Fajar; Srirahayu, Agustina; Triyono, Triyono (JMAI (Jurnal Multimedia & Artificial Intelligence), 2020)
Many variations in the clinical picture of a skin disease, and conversely one form of clinical abnormality can be found in several diseases. This kind of thing is very important to know and learn by medical health personnel, paramedics and medical and nursing students. In addition, there are many lists of diseases that must be mastered by medical doctors and medical student graduates, which are an absolute requirement that must be met. This condition requires obtaining information practically anywhere at any time. This study aims to develop an Android-based Dermatology Encyclopedia application which contains information on skin diseases that must be mastered by doctors in primary health care facilities based on Indonesian Doctor Competency Standards. The application is used to help medical personnel, young doctors (coas), medical students and ordinary people in obtaining information about skin and venereal diseases, starting from symptoms, history taking, differential diagnosis of skin diseases and providing advice on treatment or management in the form of text or images.